High Expression of MUC5AC, MUC5B, and Layilin Plays an Essential Role in Prediction in the Development of Plastic Bronchitis Caused by MPP - Ma, Yu; Gu, Yeqi; Zhang, Xinxing; Gu, Wenjing; Wang, Ting; Sun, Huiming; Dai, Yinfang; Yan, Yongdong; Wang, Yuqing; Wang, Meijuan; Sun, Huiquan; Hao, Chuangli; et al. (Frontiers in Microbiology, 2022)
Plastic bronchitis (PB) is a rare respiratory condition which can result in severe respiratory complications such as respiratory failure and death. Mycoplasma pneumoniae infection is a main etiology cause of plastic bronchitis. However, the pathogenesis of plastic bronchitis complicated by Mycoplasma pneumoniae pneumonia (MPP) has not yet been fully elucidated. Our article aims to explore biomarkers for early prediction of MPP cases complicated with plastic bronchitis. We utilized a protein chip to screen for significantly different proteins among the groups of healthy, general Mycoplasma pneumoniae pneumonia (GMPP) and refractory Mycoplasma pneumoniae pneumonia (RMPP) patients, where layilin exhibited a potent change across biology information technology. Next, we demonstrated the high expression of MUC5AC, MUC5B, and layilin in bronchoalveolar lavage fluid (BALF) of MPP cases complicated with plastic bronchitis. Further study suggested that the level of layilin had a positive correlation with both MUC5AC and MUC5B. A receiver operating characteristic (ROC) analysis was performed to assess the diagnostic values of MUC5AC, MUC5B, and layilin in MPP cases with PB. Data show that the three indicators have similar diagnostic ability for MPP children with plastic bronchitis. Then, we used different concentrations of community-acquired respiratory distress syndrome (CARDS) toxin or lipid-associated membrane proteins (LAMPs) to simulate an in vitro experiment. The in vitro assay revealed that CARDS toxin or LAMPs induced A549 cells to secrete MUC5AC, MUC5B, layilin, and proinflammatory factors. These findings suggest that MUC5AC, MUC5B, and layilin are correlated with MPP. The high expression of MUC5AC, MUC5B, and layilin play an essential role in prediction in the development of plastic bronchitis caused by MPP. The high expression of MUC5AC, MUC5B, and layilin may be relevant to the severity of illness.